ANALYSIS OF SOCIAL RETURN ON INVESTMENT (SROI) IN CREATING SHARED VALUE (CSV) ACTIVITIES IN THE “SAYURPRENEURSHIP 4.0: DIGITALIZATION STRATEGY FOR VEGETABLE TRADERS” PROGRAM - Rani Ayu Asari; Tri Siwi Agustina (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
Social Return on Investment (SROI) analysis is an important tool in measuring the social impact of a program or activity by comparing the social value generated against the costs incurred. Creating Shared Value (CSV) activities in the "Sayurpreneurship 4.0: Digitalization Strategy for Vegetable Traders" activity have the aim of improving the welfare of vegetable traders by applying digital technology and business innovation. This article will discuss how this activity not only provides economic benefits for traders, but also social contributions that have a big impact on the surrounding community. Through the SROI approach, this activity is expected to provide an overview of the social value added generated, such as increased trader income, better food accessibility, and empowerment of local communities. The methodology used is to identify, measure, and evaluate the results obtained from the implementation of digitalization in the activity "Sayurpreneurship 4.0: Digitalization Strategy for Vegetable Traders". By involving stakeholders and systematic data collection methods, the results of the analysis are expected to provide strategic recommendations for sustainable program development and have a positive impact on all parties. This analysis is expected to help program developers and investors understand the importance of social investment and the benefits of programs that promote shared value. In this case, the "Sayurpreneurship 4.0: Digitalization Strategy for Vegetable Vendors" program focuses not only on financial returns, but also on building sustainable social value for the community.